DETERMINANTS OF ADOLESCENTS SEXUAL BEHAVIOR IN THE OESAPA HEALTH CENTER WORK AREA - Laure, Endang Darmawati; Nayoan, Christina R.; Ndun, Helga J. N (Medika Alkhairaat: Jurnal Penelitian Kedokteran dan Kesehatan, 2025)
ABSTRAK Remaja telah menjadi satu masalah sosial di kalangan masyarakat, remaja memiliki risiko yang tinggi terkait dengan hubungan seksual pra nikah yang dapat menyebabkan penyebaran penyakit kelamin dan kehamilan di luar nikah atau Kehamilan yang Tidak Diinginkan (KTD). KTD terjadi setiap tahun di antara remaja perempuan berusia 15-19 tahun. Penelitian ini bertujuan untuk mengetahui determinan perilaku seksual remaja di wilayah kerja Puskesmas Oesapa. Penelitian ini adalah observasional analitik, dengan rancangan cross-sectional. Populasi dalam penelitian ini adalah remaja usia 15-19 tahun yang berada di wilayah kerja Puskesmas Oesapa berjumlah 7.059 responden. Pengambilan sampel dilakukan menggunakan teknik cluster sampling dengan besar sampel berjumlah 95 responden. Instrumen penelitian adalah kuesioner. Data dianalisis menggunakan uji Chi-square dengan tingkat kemaknaan α=0,05. Apabila nilai p < 0,05 maka, ada hubungan antara variabel dependen dengan variabel independen. Hasil analisis data menunjukkan ada hubungan antara variabel pengetahuan (p-value=0,025), peran orang tua (p-value=0,022) perilaku seksual remaja dan tidak ada hubungan antara variabel peran teman sebaya (p-value=0,434) dengan perilaku seksual remaja. Diharapkan tenaga kesehatan danrang tua perlu mengedukasi remaja terkait dampak perilaku seksual bagi remaja agar tidak melakukan perilaku seksual. ABSTRACT Premarital sexual behavior among adolescents has become a social problem in society, adolescents have a high risk associated with premarital sexual relations which can lead to the spread of sexually transmitted diseases and extramarital pregnancies or Unwanted Pregnancy (KTD). KTD occurs every year among adolescent girls aged 15-19 years. In developing countries, 55% of KTD cases end in abortions which are often unsafe (WHO, 2019). This study aims to determine the determinants of adolescent sexual behavior in the work area of ​​Oesapa Health Center. This type of research is observational analytic, with a cross-sectional design. The population in this study were adolescents aged 15-19 years who were in the work area of ​​Oesapa Health Center totaling 7,059 respondents. Sampling was conducted using cluster sampling technique with a sample size of 95 respondents. The research instrument was a questionnaire. Data were analyzed using the Chi-square test with a significance level of α = 0.05. If the p value <0.05, there is a relationship between the dependent variable and the independent variable. The results of the data analysis showed that there was a relationship between the knowledge variable (p-value = 0.025), the role of parents (p-value = 0.022) with adolescent sexual behavior and there was no relationship between the peer role variable (p-value = 0.447) with adolescent sexual behavior. It is hoped that health workers and parents to educate adolescents regarding the impact of sexual behavior on adolescents so that they do not engage in sexual behavior.